Pengaruh Pemberian Dolomit dan Pupuk NPK Terhadap Pertumbuhan dan Produksi Jagung Manis (Zea mays Saccharata sturt.) - Muhammad Suganda Koto; Ida Zulfida; Dora Silvia Dewi (JURNAL AGROPLASMA, 2023)
Sweet corn (Zea mays, Saccaharata sturt) is a food crop that is in great demand by people in Indonesia because it has a sweeter taste than ordinary corn. This sweet taste is because sweet corn has high glucose levels. The glucose content of sweet corn per 100 g has a glucose content of 16%. Sweet corn also has high nutritional content and economic value (Hidayah et al. 2020). Dolomite fertilizer is a soil savior from the onslaught of chemicals that function to neutralize soil acidity or increase soil pH. In addition to the application of dolomite fertilizer, N, P, and K fertilizers contain three macronutrients, namely nitrogen (N), phosphorus (P), and potassium (K). This research was conducted in May–July 2023 in the experimental field of the Faculty of Agriculture, Indonesian Community Development University UPMI Medan, on Jl. Pasar 12 Marindal II Village Hall, Patumbak District, Deli Serdang Regency, North Sumatra Province. This research was carried out using a randomized block design (RAK) in a factorial pattern, grouping based on Factor I: dolomite (D), which consists of 3 levels, namely: D0 = no treatment, D1 = 0.5 kg/plot, and D2 = 1 kg/plot. Factor II: application of NPK (N) fertilizer, which consists of 3 levels, namely: N0 = no treatment, N1 = 10 grams/plant, and N2 = 20 grams/plant. The single effect of applying NPK fertilizer at the level of N2 = 20 grams per plant has the effect of increasing the number of pods per sample plant based on the 5% DMRT test. The interaction effect of NPK (N) fertilizer application and dolomite fertilizer application had no effect on plant length, number of leaves, number of pods per sample plant, fruit length, or weight for sample plants.